Extracolonic manifestation of familial adenomatous polyposis in an asymptomatic patient; Literature review on current recommendation - Nik Amin Sahid; Firdaus Hayati; Ikhwan Sani; Zaidi Zakaria (2020)
Extracolonic manifestations of Familial Adenomatous Polyposis often associated with Gardner syndrome. We report a case of patient post panproctocolectomy with gastric and duodenal polyp found during upper GI scope. A rare condition which cause management dilemma as the patient asymptomatic. We review few literature regarding the latest recommendation on the management of extracolonic manifestation of FAP particularly gastric and duodenal polyposis in patient with FAP. Most expert agreed that duodenal polyposis should be manage based on Spigelman staging. For Stage 1 and Stage 2, recommended for surveillance. For Stage 3, require medical or endoscopic treatment while Stage 4, surgical option should be considered in patient age more than 35 years old.